2021
DOI: 10.21203/rs.3.rs-478044/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessment of Root Morphology and Canal Configuration of Maxillary Premolars in a Saudi Subpopulation: A Cone-Beam Computed Tomographic Study

Abstract: Background The objective of the current study was to use CBCT to look into the root canal morphology of maxillary premolars in a Saudi Arabian subpopulation and associate the results to existing canal morphology classifications. The sample size for this analysis was 500 right and left untreated maxillary premolars with fully formed roots from 250 Saudi residents (125 male and 125 female). The following observations were made using CBCT on the teeth related: (1) The number and morphology of roots; (2) The cana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The most frequent Vertucci configuration in our study was Type IV (41.3 %), followed by Type I (31.4 %). These observations are consistent with CBCT studies in populations in Spain, Brazil, China, South Africa, Saudi Arabia and Israel, which all reported that Vertucci Type IV was the most frequent configuration (over 50 %) (Abella et al;of Lima et al;Buchanan et al;Kfir et al;Al-Zubaidi et al, 2021). Our results also agree with Monardes et al, who found that the most prevalent morphological configuration in a Chilean population was 2MP B1 P1 using Ahmed's classification (Ahmed et al, 2017), equivalent to Vertucci Type IV.…”
Section: Discussionsupporting
confidence: 92%
“…The most frequent Vertucci configuration in our study was Type IV (41.3 %), followed by Type I (31.4 %). These observations are consistent with CBCT studies in populations in Spain, Brazil, China, South Africa, Saudi Arabia and Israel, which all reported that Vertucci Type IV was the most frequent configuration (over 50 %) (Abella et al;of Lima et al;Buchanan et al;Kfir et al;Al-Zubaidi et al, 2021). Our results also agree with Monardes et al, who found that the most prevalent morphological configuration in a Chilean population was 2MP B1 P1 using Ahmed's classification (Ahmed et al, 2017), equivalent to Vertucci Type IV.…”
Section: Discussionsupporting
confidence: 92%
“…e broad variety in root canal anatomy of these teeth makes conducting effective endodontic procedures the most complicated of all [18]. Several studies [19][20][21][22] reported that a high ratio of mandibular first premolars had multiple canals. Different ethnic or geographic groups can have different rates, locations, and morphologies of root canal systems [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [19][20][21][22] reported that a high ratio of mandibular first premolars had multiple canals. Different ethnic or geographic groups can have different rates, locations, and morphologies of root canal systems [19][20][21][22]. Mandibular premolars with two or more canals were observed in 13.7% of American people [19] and 46% of the Chinese population [20].…”
Section: Introductionmentioning
confidence: 99%